Waqf and State Interference: A Phenomenology Study in Al-Azhar University, Egypt - Agung Abdullah (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This paper was aimed at revealing the Egyptian Government's intervention in the management of Al-Azharwaqf. The data was collected by interviewing officials at the Al-Azhar University in Egypt, officials at the Egyptian Ministry of Education, academics and Waqf researchers in Egypt. The results of this study indicated that Egyptian Government intervened and took over the management of Al-Azharwaqf by issuing laws related to waqf and its management from 1923 to 1971. The impact of the takeover of Al-Azharwaqf management by the State also made Al-Azhar was no longer economically independent and was held hostage by the government.